Implementasi Program Konversi Data Pesanan Berbasis Spreadsheet Ke Database MySQL untuk Digitalisasi Administrasi pada UMKM CV. Karya Mandiri - Rama Nittia Khadifa; Farizi Ilham; Robi Farhan Anshori; Humaidah (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2026)
CV. Karya Mandiri is a trading company specializing in staple goods that has been in operation since 1994 and employs approximately 35 people. In its day-to-day operations, particularly in order data management and administration, the company still relies on a manual spreadsheet-based system. This has led to several issues, such as data inconsistencies, time-consuming record-keeping processes, and the risk of errors in data processing. The objective of this internship is to implement a program for converting order data from spreadsheets into a MySQL database in order to improve the efficiency, accuracy, and security of administrative data. The methods used include observation, interviews, and literature review, as well as system development using the SDLC method with a waterfall approach, which encompasses the analysis, design, implementation, and testing phases. The scope of the system includes the conversion of spreadsheet data into a database, structured data storage, and more integrated order data management. The expected outcomes of this system are to minimize data entry errors, speed up the report generation process, and support the digitization of administrative processes at CV. Karya Mandiri.